2012
DOI: 10.1159/000335702
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Diverticular Disease: Abnormalities of Neuromuscular Function

Abstract: Although diverticular disease of the colon (diverticulosis) is a frequent finding in Western countries, its pathophysiologic grounds are still only partially understood. Traditionally considered as an age-related condition, colonic diverticulosis is probably the final result of several factors concurring together to determine the anatomo-functional abnormalities eventually causing outpouching of the viscus’ mucosa. Among these factors, a relevant role seems to be played by an abnormal neuromuscular function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 90 publications
1
19
0
1
Order By: Relevance
“…Of note, patients with DD have been shown to display an increase in both overall and rhythmic colonic contractions [2], [46]. Since studies on rat [47] and human [48] colonic muscle have suggested that ICCs are likely to inhibit colonic motility by nitric oxide release, the reduction of intramuscular ICC, as observed in the colon of DD patients, might result in an increment of SMC contractility, as repeteadly observed in these patients [4].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of note, patients with DD have been shown to display an increase in both overall and rhythmic colonic contractions [2], [46]. Since studies on rat [47] and human [48] colonic muscle have suggested that ICCs are likely to inhibit colonic motility by nitric oxide release, the reduction of intramuscular ICC, as observed in the colon of DD patients, might result in an increment of SMC contractility, as repeteadly observed in these patients [4].…”
Section: Discussionmentioning
confidence: 91%
“…Its pathogenesis is likely multifactorial in nature, involving dietary habits as well as changes in colonic pressure, motility and wall structure associated with ageing [1]. Abnormalities of colonic motility, including increments of the overall motor activity, as well as abnormal responses to physiologic stimuli and retro-propagation of mass movements, might predispose to the formation of pulsion diverticula by herniation of colonic wall [2][4].…”
Section: Introductionmentioning
confidence: 99%
“…19–25 Most of these studies measured pressures in the rectum or rectosigmoid junction, and they were commonly underpowered and limited by selection bias. 26 No study measured colonic motility prior to the development of diverticula.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that age related changes in collagen composition led to the formation of diverticular disease [3]. In addition, abnormalities in myoelectrical and motor function in the large bowel were considered as potential etiological factors [4]. In particular, recent investigations observed significantly decreased numbers of Cajal 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 cells in colonic diverticular specimen [5].…”
Section: Introductionmentioning
confidence: 99%